2014
DOI: 10.1002/ejic.201402814
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Structure, and Electrical Characterization of (SnSe)1.2TiSe2

Abstract: Keywords: Layered compounds / Thin films / Electronic structure / Thermoelectric materials / Charge transfer (SnSe) 1.2 TiSe 2 was found to self-assemble from a precursor containing modulated layers of Sn-Se and Ti-Se over a surprisingly large range of layer thicknesses and compositions. The constituent lattices form an alternating layer superstructure with rotational disorder present between the layers. This compound was found to have the highest Seebeck coefficient measured for analogous TiX 2 containing mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
74
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(93 citation statements)
references
References 40 publications
18
74
1
Order By: Relevance
“…Using the relationship derived by Parratt and estimating that Kiessig fringes are no longer visible at approximately 12 o 2θ, we estimate the average roughness of the films to be near 1.2 Å. 35,36 While the variation in the position of the reflections and therefore unit cell sizes is small, there are pronounced changes in the relative intensities of reflections in the diffraction patterns. Since the diffracted intensity in these specular XRD patterns is proportional to the Fourier transform of the electron density profile along the axial direction, the variation in relative intensities reflects the different stacking sequence of the constituents in the isomeric intergrowths.…”
Section: Methodsmentioning
confidence: 99%
“…Using the relationship derived by Parratt and estimating that Kiessig fringes are no longer visible at approximately 12 o 2θ, we estimate the average roughness of the films to be near 1.2 Å. 35,36 While the variation in the position of the reflections and therefore unit cell sizes is small, there are pronounced changes in the relative intensities of reflections in the diffraction patterns. Since the diffracted intensity in these specular XRD patterns is proportional to the Fourier transform of the electron density profile along the axial direction, the variation in relative intensities reflects the different stacking sequence of the constituents in the isomeric intergrowths.…”
Section: Methodsmentioning
confidence: 99%
“…As with the thermodynamically stable misfit compounds, however, materials based on TiSe 2 have shown to produce carrier concentrations on the order of 10 21 cm −3 , with high Seebeck coefficients and in-plane resistivity values on the order of 10 −5 Ωm. To date, (SnSe) 1.2 TiSe 2 , (PbSe) 1+δ (TiSe 2 ) n (n = 1, 2) and (BiSe) 1.15 TiSe 2 have all been reported [77,86,88,92]. For TiSe 2 based compounds, the only direct comparison between a ferecrystal and a misfit compound is for [(PbSe)] 1.16 (TiSe 2 ) 2 [65,86].…”
Section: Ferecrystalsmentioning
confidence: 99%
“…This system was chosen because previous investigations of (Pb x Sn 1− x Se) 1 (TiSe 2 ) 1 showed that a solid solution could be formed over the entire composition range, even though the bulk phase diagram of Pb x Sn 1− x Se shows a miscibility gap . Previous investigations also determined that both SnSe and PbSe form distorted rock salt structures when layered with TiSe 2 , and that the structures of the SnSe and PbSe both change as their layer thicknesses are increased . Herein, we show that, while surface segregation does not occur in bilayers of Pb x Sn 1− x Se alloys, when the thickness is larger than a bilayer a segregation of Pb to the interface is apparent using several different experimental techniques.…”
Section: Figurementioning
confidence: 64%